ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN TIGA TAHUN SEBELUM DAN TIGA TAHUN SESUDAH PENERAPAN INTERNET BANKING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Ike Roudhotul Ulfa; Abdul Qodir Djaelani; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis research aims to find out the impact of internet banking application thecompany banking. With research periods are 3 years before and 3 years after theapplication of internet banking .The analysis of financial performance in terms ofvarious aspects based on the purpose of internet banking application, includes:increase the funding source (Third Party Funds), decrease the operational cost,decrease the credit risk, and increase the profitability. The results of normalitytest show that variables tested by paired sample T- test method are the ratio ofThird Party Funds (DPK), laborcost ratio, and the ratio of Return On Asset(ROA). While variables tested by wilcoxon signed rank test method are the ratioof Non Performing Loan (NPL), operating cost ratio, and the ratio of Fee BasedIncome (FBI).Laborcost ratio and Operational Efficiecy show an improvement after theimplementation of internet banking although the results of the comparison showno significant difference between before and after applying internet banking.While the DPK, FBI ratio and NPL ratio have significant and negative results.ROA ratio shows a significant and positive difference which means there is animprovement in getting return on asset after the application of internet banking.Keyword:Purpose of Internet Banking, Financial Performance, DPK, laborcost,Operational Efficiency, NPL, FBI, ROA.